2021
DOI: 10.24156/jikk.2021.14.3.282
|View full text |Cite
|
Sign up to set email alerts
|

Problems, Stress, Social Support, and Coping Strategies During the Covid-19 Pandemic: Case of International College Students in Indonesia

Abstract: Covid-19 has an impact on various areas of life in all walks of life. This condition also has an impact on students, especially in their education. This study aimed to analyze the effect of problems, stress levels, and social support on the coping strategies of international students in Indonesia during the Covid-19 pandemic. This study used a cross-sectional design with a quantitative approach—data were collected for two months, June-July 2020. The sample of this study was 88 foreign nationals who studied in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
3
7
0
Order By: Relevance
“…In addition to peers, three out of four students choose their parents as parties who assist in facing problems. This result is in line with previous research, which states that social support, especially from family and friends, can reduce the problems felt (Amalia & Rahmatika, 2020;Defina & Rizkillah, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition to peers, three out of four students choose their parents as parties who assist in facing problems. This result is in line with previous research, which states that social support, especially from family and friends, can reduce the problems felt (Amalia & Rahmatika, 2020;Defina & Rizkillah, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, more than half conducted strategies by trying to strengthen themselves and be grateful every time. This result aligns with previous research that international students' most frequently used coping strategies is to pray and be grateful to all (Defina & Rizkillah, 2021). Immanuel et al (2021) also stated that active coping and emotional management by changing positive thinking could reduce stress in dealing with difficult events.…”
Section: Discussionsupporting
confidence: 89%
“…The results of this study found that the stressors for the elderly, both male and female, were classified as low and there was no significant difference between male and female stressors. This is in line with the results of research by Defina and Rizkillah (2021) which state that there is no significant difference in stress between women and men. According to Santoso and Tjhin (2018), various factors that can reduce stressors are positive changes that occur in life such as the birth of new family members, family members who excel, health improvements, and/or daily events.…”
Section: Discussionsupporting
confidence: 92%
“…Exclusion and inequality are likely to worsen, especially among already disadvantaged and vulnerable populations (Yarrow, Masood, & Afkar, 2020). Several studies pointed out the once‐face‐to‐face educational style has evolved into an online one that stresses certain students, with almost 50% experiencing severe stress (Defina & Rizkillah, 2021; Nursalim et al, 2021; Saroinsong et al, 2020; Wahyu & Simanullang, 2020). Therefore, indicating any positive factor, including preventive factors, might be the key to supporting students' recovery period as their creation of resilience.…”
Section: Introductionmentioning
confidence: 99%